The prospects of use of upland rice in the Rostov region - P. I. Kostylev; E. V. Krasnova; A. A. Redkin; Yu. P. Kalievskaya (Зерновое хозяйство России, 2018)
The article deals with the review of the breeding work in the development of upland rice varieties in the Rostov region during the years of 2002-2015. Because of the deficit of water the problem is of great importance the last years. The staff of the laboratory of rice of I.G. Kalinenko ARRIGC has studied the collection of ARIR from which they have taken such varieties tolerant to water deficit as ‘Chan-Chun-Man’, ‘Din Syan’, ‘Sukhodolny’, ‘Bely SKOMS’, etc. They are of low height, with a thin stalk, a small panicle and average heads; they are resistant to fall and to lodging and they are early maturing varieties. The hybrids on 28 combinations and the lines of rice for growing under periodic irrigation have been obtained from the crossing of upland rice samples with such varieties of Don breeding as ‘Razdolny’, ‘Boyarin’ and ‘Komandor’. After multiple choices of recombinant forms the best lines have been assessed in the control farm. Their productivity, as a rule, was the same as of the standard varieties. The sample ‘9497’ (‘Chan-Chun-Man’x‘Boyarin’) produced 7.57 t/ha for six years, that exceeded the productivity of the standard variety ‘Boyarin’ on 0.57 t/ha. In 2015 the sample ‘5782’ (‘Komandor’x‘Chan-Chun-Man’) produced 8.52 t/ha (on 0.86t/ha more than the standard). We cooperate with ARRI of irrigated agriculture (Volgograd) and annually carry out the testing of the best lines. We also work in cooperation with the Institute of Rice (Ukraine, Skadovsk), with ARRIGM’s affiliate in Kalmykiya, where we carried out the agroecological testing of promising lines of rice under rain irrigation. In 2016 there was laid down an experimental plot with periodic irrigation for the testing of upland samples of rice developed in ARRIGC, ARRIOA and ARRIR and for selection of the most stable and productive forms.